Learning Foreign Languages Through Blended Learning - Basori Basori (Scope : Journal of English Language Teaching, 2018)
ABSTRACT. Blended learning is gaining popularity as an effective method to deliver courses. Foreign language instruction is adopting opportunities to apply blended learning. This paper looks at the essence of blended learning and foreign language instruction by defining those two terms. The literature has clearly unveiled the principles of each learning method that constitutes foreign language delivered via blended learning. It leads to major elements that need to be considered when designing blended foreign language instruction. Sufficient input, adequate interaction, plenty of feedback, and meaningful tasks are major components of building blended foreign language courses. Some recent studies have successfully implemented those principles in designing blended learning foreign language instruction; however, the studies also disclose some challenges.  Keywords: Blended learning, foreign language learning, foreign language instructions   ABSTRAK Blended learning semakin populer sebagai metode yang efektif dalam kegiatan pengajaran. Metode ini juga diterapkan dalam pengajaran bahasa asing. Artikel ini membahas esensi blended learning dan pengajaran bahasa asing dengan mendefinisikan kedua istilah tersebut. Telah banyak studi literatur yang membahas dan mendiskusikan tentang prinsip-prinsip metode pembelajaran bahasa asing yang disampaikan melalui blended learning. Ini mengarah pada elemen-elemen inti yang perlu dipertimbangkan dalam merancang pengajaran bahasa asing yang disampaikan melalui blended learning. Input yang cukup, interaksi yang memadai, adanya umpan balik yang memadai, dan tugas yang bermakna adalah komponen-komponen utama yang perlu diperhatikan dalam pengajaran bahasa asing yang menerapkan blended learning. Beberapa studi terbaru telah berhasil menerapkan prinsip-prinsip tersebut dalam merancang pembelajaran bahasa asing yang menerapkan blended learning. Di sisi yang lain, artikel ini juga memaparkan beberapa tantangan pengajaran bahasa asing yang menerapkan metode blended learning. Kata kunci: blended learning, pembelajaran bahasa asing, pengajaran bahasa asing